PENGARUH PEMAHAMAN GURU TENTANG PENDIDIKAN KARAKTER TERHADAP PELAKSANAAN PENDIDIKAN KARAKTER PADA MATA PELAJARAN SOSIOLOGI - Emiasih, Dewi (Komunitas, 2011)
Integrasi muatan pendidikan karakter di sekolah-sekolah merupakan hal yang baru dimplementasikan di lingkungan pendidikan Kabupaten Pekalongan. Pendidikan karakter masih banyak mengahadapi kendala dalam pelaksanaannya terutama dalam hal pemahaman guru tentang pendidikan karakter. Pemahaman guru tentang pendidikan karakter akan berpengaruh terhadap pelaksanaan pendidikan karakter di dalam kelas. Permasalahan yang diangkat dalam penelitian ini adalah adakah pengaruh pemahaman guru tentang pendidikan karakter terhadap pelaksanaan pendidikan karakter pada pelajaran Sosiologi di Pekalongan. Responden dalam penelitian ini adalah guru mata pelajaran Sisiologi di Kabupaten Pekalongan yang berjumlah 38 guru. Hasil penelitian ini menunjukkan ada pengaruh antara pemahaman guru tentang pendidikan karakter terhadap pelaksanaan pendidikan karakter pada mata pelajaran Sosiologi di Kabupaten Pekalongan sebesar 14,3%, artinya ada pengaruh yang signifikan antara pemahaman guru tentang pendidikan karakter terhadap pelaksanaan pendidikan karakter pada mata pelajaran Sosiologi di Kabupaten Pekalongan.The integration of character education in schools is a new thing just implemented in Pekalongan educational system. Character education is still facing many obstacles in its implementation, especially in terms of teachers’ understanding of character education. Teachers’ understanding definitely affects the implementation of character education in the classroom. The main question discussed in this article is how teachers’ understanding of character education effeccts the implementation of character education on the subjects of sociology. The purpose of this study was to determine whether there is influence between teachers’ understanding of character education on the implementation of character education on the subjects of Sociology and to find out how much influence. Respondents in this study are Sociology teachers in the district of Pekalongan Sisiologi, that has total number of 38 teachers. The results of this study show that there is positive corelation between teachers ‘understanding of character education on the implementation of character education on the subjects of Sociology in Pekalongan District with score 14.3%. This means that the effect between teachers’ understanding of character education on the implementation of character education on the subjects of Sociology is really significant.